The Norton field guide to writing, with handbook / Richard H Bullock; Francine Weinberg - Bullock, Richard H
With just enough detail -- and color-coded links that send students to more detail if they need it -- this is the rhetoric that tells students what they need to know and resists the temptation to tell them everything there is to know. Designed for easy reference -- with menus, directories, and a combined glossary/index. The Third Edition has new chapters on academic writing, choosing genres, writing online, and choosing media, as well as new attention to multimodal writing.